Moderating effect of government policy on entrepreneurship and growth performance of small-medium enterprises in Cambodia - Mohd Shariff, Mohd Noor; Chea, Peou; Ali, Juhary (Society for Alliance, Fidelity and Advancement (SAFA), 2010)
The role of Small-Medium Enterprises has been recognized to be importance as an engine of growth and poverty alleviation through the creation of jobs and income for the people.The aims of this study are to examine the moderating effect of government policy on the relationship between entrepreneurial values, firm financing,management, market practices and growth performance of SMEs in Cambodia.The survey method was used to gather 220 usable questionnaires from SME owner-managers in the City of Phnom Penh in Cambodia. Hierarchical multiple regression analysis was performed to determine the results. The results of the study showed a positive relationship between entrepreneurial values, firm financing, management, market practices and SME growth performance as hypothesized.The results also confirm that government policy have an important role as full moderator in such relationships.In addition, implications to growth theory and practice, limitations, and suggestions for future research were also discussed.